Strategic analysis of the drought resilience of water supply systems. (12th December 2022) - Murgatroyd, Anna; Gavin, Helen; Becher, Olivia; Coxon, Gemma; Hunt, Doug; Fallon, Emily; Wilson, Jonny; Cuceloglu, Gokhan; Hall, Jim W.
Abstract : Severe droughts can result in shortages of water supplies, with widespread social and economic consequences. Here we use a coupled simulation model to assess the reliability of public water supplies in England, in the context of changing scenarios of water demand, water regulation and climate change. The coupled simulation model combines climate simulations, a national-scale hydrological model and a national-scale water resource systems model to demonstrate how extreme meteorological droughts translate into hydrological droughts and water shortages for water users. We use this model to explore the effectiveness of strategic water resource options that are being planned in England to secure water supplies to most of England's population up to a drought return period of 1 in 500 years. We conclude that it is possible to achieve a 1-in-500-years standard in locations where strategic resource options are used, while also reducing water abstraction to restore the aquatic environment. However, the target will be easier to achieve if effective steps are also taken to reduce water demand. This article is part of the Royal Society Science+ meeting issue 'Drought risk in the Anthropocene'.